Evaluation of neurological disorders that develop concurrently with COVID-19 pneumonia: a retrospective analysis - TASCI, Irem; BALGETIR, Ferhat; MUNGEN, Bulent; DEMIR, Caner Feyzi; GONEN, Murat; DELEN, Leman Acun; KURT, Osman (Arquivos de Neuro-Psiquiatria, 2022)
Background: During the pandemic, many neurological symptoms have been evaluated as complications of COVID-19 pneumonia. Objective: To investigate the frequency and characteristics of neurological findings, and their effects on the prognosis of patients with COVID-19 pneumonia who consulted with the Neurology department. Methods: Data on 2329 patients who were hospitalized with the diagnosis of COVID-19 pneumonia in our hospital were scanned. The clinical, laboratory and radiological findings relating to treatment of 154 patients who required neurological consultation were retrospectively evaluated by reviewing the clinical notes. Results: The number of COVID-19 pneumonia patients who required neurological consultations while hospitalized in the ICU was 94 (61.0%). The most common symptom among these patients was hyperactive delirium. Mean age, ferritin levels and CRP values of those with delirium were higher, while the mean lymphocyte percentage were lower, than those of the patients without delirium. Epileptic seizures were observed in eight patients without an epilepsy diagnosis. Two patients were diagnosed with GBS and one patient with ICU neuropathy. The D-dimer levels of patients with acute hemorrhagic CVD and the thrombocyte levels of patients with acute ischemic CVD were found to be higher than in patients without acute ischemic CVD. Conclusion: The proportion of patients who required neurological consultations was higher in the ICUs. We observed neurological symptoms more frequently in the advanced age group. There were no significant increases in the incidence of other neurological conditions except delirium, in COVID-19 patients. We think that further studies are needed to support our data.
Keywords: COVID-19; Neurology; Referral and Consultation; Central Nervous System Diseases; Peripheral Nervous System Diseases